Relationship of in vitro and in planta screening: improving the selection process for biological control agents against Fusarium root rot in row crops. (25th February 2018) - Parikh, L.; Eskelson, M. J.; Adesemoye, A. O.
Abstract: Fusarium root rot in row crops is typically managed by cultural practices and fungicide seed treatments. Biological control using microbial agents is another option but needs further development for improved disease management. Screening to identify biocontrol agents are crucial. However, relationships among the steps and how to improve the screening process are unresolved questions. Strains of Burkholderia (4), Bacillus (5) and Trichoderma (26) were studied in vitro against six Fusarium pathogens. All the bacteria and five selected Trichoderma strains were tested in planta in the greenhouse against diseases of Fusarium graminearum and Fusarium oxysporum . Burkholderia ambifaria C628, Bacillus simplex R180, and all Trichoderma isolates showed high reduction in disease levels in corn, soybean and wheat, ranging from 16 to 63%. Responses of the biocontrol agents during in vitro and in planta screening did not always correlate. In vitro and in planta tests should be considered independently in selecting biocontrol candidates.